Placental oxygen transport estimated by the hyperoxic placental BOLD MRI response. Issue 10 (14th October 2015) - Sørensen, Anne; Sinding, Marianne; Peters, David A.; Petersen, Astrid; Frøkjær, Jens B.; Christiansen, Ole B.; Uldbjerg, Niels
Abstract: Estimating placental oxygen transport capacity is highly desirable, as impaired placental function is associated with fetal growth restriction (FGR) and poor neonatal outcome. In clinical obstetrics, a noninvasive method to estimate the placental oxygen transport is not available, and the current methods focus on fetal well‐being rather than on direct assessment of placental function. In this article, we aim to estimate the placental oxygen transport using the hyperoxic placental blood oxygen level‐dependent (BOLD) magnetic resonance imaging (MRI) response. In 21 normal pregnancies and in four cases of severe early onset FGR, placental BOLD MRI was performed in a 1.5 Tesla MRI system (TR:8000 msec, TE:50 msec, Flip angle:90). Placental histological examination was performed in the FGR cases. In normal pregnancies, the average hyperoxic placental BOLD response was 12.6 ± 5.4% (mean ± SD). In the FGR cases, the hyperoxic BOLD response was abnormal only in cases with histological signs of maternal hypoperfusion of the placenta. The hyperoxic placental BOLD response is mainly derived from an increase in the saturation of maternal venous blood. In the normal placenta, the pO2 of the umbilical vein is closely related to the pO2 of the uterine vein. Therefore, the hyperoxic placental BOLD response may reflect the placental oxygen supply to the fetus. In early onset FGR, the placental oxygen transport is reduced mainly because of the maternal hypoperfusion, and in these cases the placental BOLD response might be altered. Thus, the placental BOLD MRI might provide direct noninvasive assessment of placental oxygen transport. Abstract : The hyperoxic placental BOLD response is abnormal in cases of fetal growth restriction. This finding might be explained by the alterred placental oxygen transport capasity in FGR cases.